Past, Present, and Future of Informed Consent in Pain and Genomics Research: Challenges Facing Global Medical Community. Issue 1 (26th August 2016) - Compagnone, Christian; Schatman, Michael E.; Rauck, Richard L.; Van Zundert, Jan; Kraus, Monika; Primorac, Dragan; Williams, Frances; Allegri, Massimo; Saccani Jordi, Gloria; Fanelli, Guido; ,
Abstract: In recent decades, there has been a revision of the role of institutional review boards with the intention of protecting human subjects from harm and exploitation in research. Informed consent aims to protect the subject by explaining all of the benefits and risks associated with a specific research project. To date, there has not been a review published analyzing issues of informed consent in research in the field of genetic/Omics in subjects with chronic pain, and the current review aims to fill that gap in the ethical aspects of such investigation. Despite the extensive discussion on ethical challenges unique to the field of genetic/Omics, this is the first attempt at addressing ethical challenges regarding Informed Consent Forms for pain research as the primary focus. We see this contribution as an important one, for while ethical issues are too often ignored in pain research in general, the numerous arising ethical issues that are unique to pain genetic/Omics suggest that researchers in the field need to pay even greater attention to the rights of subjects/patients. This article presents the work of the Ethic Committee of the Pain‐Omics Group (www.painomics.eu ), a consortium of 11 centers that is running the Pain‐Omics project funded by the European Community in the 7th Framework Program theme (HEALTH.2013.2.2.1‐5—Understanding and controlling pain). The Ethic Committee is composed of 1 member of each group of the consortium as well as key opinion leaders in the field of ethics and pain more generally.